2017
DOI: 10.1002/glia.23107
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic IP3Rs: Contribution to Ca2+ signalling and hippocampal LTP

Abstract: Astrocytes regulate hippocampal synaptic plasticity by the Ca dependent release of the N-methyl d-aspartate receptor (NMDAR) co-agonist d-serine. Previous evidence indicated that d-serine release would be regulated by the intracellular Ca release channel IP receptor (IP R), however, genetic deletion of IP R2, the putative astrocytic IP R subtype, had no impact on synaptic plasticity or transmission. Although IP R2 is widely believed to be the only functional IP R in astrocytes, three IP R subtypes (1, 2, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 67 publications
(111 reference statements)
6
119
1
Order By: Relevance
“…1h,l), which largely mediates G-protein-mediated calcium elevation in astrocytes, thus suggesting that synaptic regulation requires the elevation of calcium levels in astrocytes. Because other types of IP 3 receptors have recently been shown to contribute to astrocyte calcium mobilization 43 , we further tested the astrocytic calcium dependency by loading astrocytes with the calcium chelator BAPTA, by whole-cell patch-clamping astrocytes with a solution containing 40 mM BAPTA. Astrocytes are known to be gap-junction coupled in different brain areas, which allows the diffusion of BAPTA in the astrocytic network from single recorded astrocytes 44, 45 .…”
Section: Resultsmentioning
confidence: 99%
“…1h,l), which largely mediates G-protein-mediated calcium elevation in astrocytes, thus suggesting that synaptic regulation requires the elevation of calcium levels in astrocytes. Because other types of IP 3 receptors have recently been shown to contribute to astrocyte calcium mobilization 43 , we further tested the astrocytic calcium dependency by loading astrocytes with the calcium chelator BAPTA, by whole-cell patch-clamping astrocytes with a solution containing 40 mM BAPTA. Astrocytes are known to be gap-junction coupled in different brain areas, which allows the diffusion of BAPTA in the astrocytic network from single recorded astrocytes 44, 45 .…”
Section: Resultsmentioning
confidence: 99%
“…KO studies have suggested that, first, it modulates mainly somatic Ca 2+ transients (Srinivasan et al 2015), and second, that it does not regulate neuronal excitability, synaptic transmission and plasticity, neurovascular coupling or behaviour (Petravicz et al 2008, 2014; Agulhon et al 2010; Nizar et al 2013; Bonder and McCarthy 2014). Alternative mechanisms to induce Ca 2+ rises have been proposed, such as other IP3Rs or transient receptor potential cation channels A1 (TRPA1) (Shigetomi et al 2011; Sherwood et al 2017). As discussed, the emerging view that Ca 2+ signalling might be compartmentalised suggests that Ca 2+ elevations may be triggered through different pathways in the soma, branches and processes (Bazargani and Attwell 2016).…”
Section: Functional Properties Of Human Astrogliamentioning
confidence: 99%
“…65 Based on previous findings precisely demonstrating in vitro that glia may release D-serine through a Ca 2+regulated process, 66,67 it was claimed that astrocytic IP3 receptors contribute to the astrocyte release of D-serine thereby controlling functional plasticity at synapses. 65 Based on previous findings precisely demonstrating in vitro that glia may release D-serine through a Ca 2+regulated process, 66,67 it was claimed that astrocytic IP3 receptors contribute to the astrocyte release of D-serine thereby controlling functional plasticity at synapses.…”
Section: Poisoning and Pharmacological Rescue Experimentsmentioning
confidence: 99%